1999
DOI: 10.1007/s002210050884
|View full text |Cite
|
Sign up to set email alerts
|

Direction information coordinated via the posterior third of the corpus callosum during bimanual movements

Abstract: We examined bimanual coordination in a patient before and after each stage of callosotomy surgery. We tested how well the patient coordinated movement direction between the hands. The patient drew symmetrical or asymmetrical figures simultaneously with both hands. Before surgery, symmetrical figures were drawn well and asymmetrical figures were drawn poorly. Following anterior callosotomy, the drawings improved slightly. Symmetrical figures were still drawn well, and asymmetrical ones were still drawn poorly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 29 publications
5
56
0
Order By: Relevance
“…In contrast, control subjects exhibited interference on all of these measures when producing asymmetric shapes. These results indicate that interference based on the spatial characteristics of the movements arises through callosally mediated interactions, consistent with the notion that the spatial goals are established at a cortical level (see also Eliassen et al 1999;Kennerley et al 2002).…”
Section: Introductionsupporting
confidence: 86%
“…In contrast, control subjects exhibited interference on all of these measures when producing asymmetric shapes. These results indicate that interference based on the spatial characteristics of the movements arises through callosally mediated interactions, consistent with the notion that the spatial goals are established at a cortical level (see also Eliassen et al 1999;Kennerley et al 2002).…”
Section: Introductionsupporting
confidence: 86%
“…This is in disagreement with a previous work showing the importance of posterior corpus callosum in bimanual coordination (Eliassen et al, 2000); however, whereas visual information was used in this experimental paradigm, in our study, subjects performed acoustically paced motor tasks without any visual facilitation. Furthermore, it was found that visual and visuospatial integration is disrupted by posterior callosotomy (Gazzaniga and Freedman, 1973;Sidtis et al, 1981;Volpe et al, 1982;Risse et al, 1989;Eliassen et al, 1999;Marzi et al, 1999), whereas timing coordination is altered by anterior callosotomy (Preilowski, 1972(Preilowski, , 1975Eliassen et al, 1999). Also, the evaluation of the crossed-uncrossed difference in simple reaction times with visual stimuli, to measure the interhemispheric transmission time, cannot be extended to auditory stimuli because there is an almost simultaneous access of auditory information to both hemispheres (Iacoboni and Zaidel, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This notion was built mainly on bimanual coordination deficits observed in patients with extensive lesions of the CC or partial callosotomies (Preilowski, 1972;Jeeves et al, 1988;Andres et al, 1999;Eliassen et al, 1999Eliassen et al, , 2000Wiesendanger and Serrien, 2004;Caille et al, 2005). One step toward a refined understanding of the function of the human CC would be to identify its detailed topographical organization by novel MRI techniques.…”
Section: Introductionmentioning
confidence: 99%